"Accutane Check": Insights into youth sentiment toward isotretinoin from a TikTok trend. Issue 4 (14th June 2021) - Galamgam, Jayden; Jia, Justin L.
Abstract: Social media platforms such as TikTok allow patients to exchange and share health information. In this study, we sought to understand how teenagers and young adults utilize TikTok to engage with acne and isotretinoin information. Analysis of the top 50 TikTok videos on an isotretinoin trend demonstrated over 18‐million likes and 137‐thousand comments. Most videos focused on before and after improvement in acne severity while video comments primarily discussed side effects and personal anecdotes. Dermatologists should be aware of trending content on social media to better understand how youth patients and patient's families may receive medical information regarding isotretinoin outside of dermatology clinics.